2020
DOI: 10.3389/fphys.2020.01115
|View full text |Cite
|
Sign up to set email alerts
|

No Association Between T-peak to T-end Interval on the Resting ECG and Long-Term Incidence of Ventricular Arrhythmias Triggering ICD Interventions

Abstract: Background and Objectives Potential of using the T-peak to T-end (TpTe) interval as an electrocardiographic parameter reflecting the transmural dispersion of ventricular repolarization (TDR) to identify patients (pts.) with higher risk of malignant ventricular arrhythmias (MVA) for better selection of candidates for implantable cardioverter-defibrillator (ICD) in primary prevention (PP) of sudden cardiac death (SCD) remains controversial. The primary objective of this study was to investigate the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 37 publications
0
3
0
Order By: Relevance
“…Furthermore, these findings were validated in an independent cohort. Interestingly, in our participants in the derivation and validation cohorts at supine rest, the maximal Tp-e was never localized in leads V5 or V6, even though these leads have been among those selected for Tp-e measurement in several studies 9,[12][13][14] , including studies that did not find an association between Tp-e length and risk of ventricular arrhythmias or sudden cardiac death 26,27 .…”
Section: Discussionmentioning
confidence: 91%
“…Furthermore, these findings were validated in an independent cohort. Interestingly, in our participants in the derivation and validation cohorts at supine rest, the maximal Tp-e was never localized in leads V5 or V6, even though these leads have been among those selected for Tp-e measurement in several studies 9,[12][13][14] , including studies that did not find an association between Tp-e length and risk of ventricular arrhythmias or sudden cardiac death 26,27 .…”
Section: Discussionmentioning
confidence: 91%
“…Furthermore, these findings were validated in an independent cohort. Interestingly, in our participants in the derivation and validation cohorts at supine‐rest, the maximal Tp‐e was never localized in leads V5 or V6, even though these leads have been among those selected for Tp‐e measurement in several studies (Shimizu et al, 2002 ; Panikkath et al, 2011 ; Lubinski et al, 1998 ; Bachmann et al, 2016 ), including studies that did not find an association between Tp‐e length and risk of ventricular arrhythmias or sudden cardiac death (Michalek et al, 2020 ; Porthan et al, 2013 ).…”
Section: Discussionmentioning
confidence: 99%
“…T peak-end has been a topic for discussion in relation to repolarization heterogeneity in recent literature (Malik et al, 2019). Studies report a relation between T peak-end and arrhythmia risk in patients with heart failure (Rosenthal et al, 2015), ischemic heart disease (Shenthar et al, 2015) and BrS (Castro Hevia et al, 2006), although other studies contradict that prolonged T peak-end interval is proarrhythmic (Michalek et al, 2020;O'Neal et al, 2017). We have previously shown that the onset of the electrocardiographic T wave occurs before first measured RT and that 75% of recording sites repolarized after T peak (Meijborg et al, 2014).…”
Section: T Peak-end and T Widthmentioning
confidence: 99%